Computed tomographic colonography for symptomatic patients: the diminutive polyp dilemma. Issue 4 (9th November 2022) - Hadjittofi, Christopher; Sharma, Vivek; Bhatt, Dhaara; Rifai, Tamam; Williams, Stuart; Shaikh, Irshad
Abstract: Background: Computed tomographic colonography (CTC) is sensitive to polyp detection but is considered inaccurate for measuring diminutive polyps (<6 mm), with divergence between CTC and either colonoscopic or histopathological polyp measurements. Reporting diminutive polyps remains debatable. This study aims to compare outcomes of symptomatic patients with diminutive versus borderline polyps on CTC and to thereby examine the potential implication of reporting diminutive polyps. Methods: A single‐centre retrospective study of symptomatic patients who underwent CTC from October 2016 through September 2018 was performed. After excluding CTC demonstrating cancer, no polyps, or polyps >6 mm, cases were categorized as either 'diminutive' (largest polyp <6 mm), or 'borderline' (largest polyp = 6 mm). The outcome measures were progression to endoscopy, surgery, procedure‐related morbidity, dysplasia and malignancy. Results: A total of 308 cases (211 diminutive and 97 borderline) were analysed. The groups were similar ( P  > 0.05) in mean age (73 vs. 74 years), female proportion (57% vs . 49%), endoscopy‐related morbidity (6% vs . 7%) and CTC‐related morbidity (0 vs . 1%). Most patients (64%) underwent endoscopy, which was more common in the borderline vs . the diminutive group (76% vs . 59%; P  = 0.003). Dysplasia was more common in the borderline vs . the diminutive group (69% vs . 48%; P  = 0.003). No malignancies were diagnosed, and no patients proceeded to surgery. Conclusion: Reporting diminutive polyps on CTC for symptomatic patients frequently leads to endoscopy, which often reveals dysplasia but rarely malignancy. This raises the question of how referring clinicians can best counsel and manage symptomatic patients with diminutive polyps on CTC, by considering the balance between utilitarianism and deontology. Abstract : This is a single‐centre experience in the radiological detection of diminutive colonic polyps in a cohort of 308 symptomatic patients (211 patients with at least one diminutive (<6 mm) polyp and 97 patients with borderline (6 mm) polyps). We found that most symptomatic patients with diminutive polyps on CT colonography proceed to endoscopy, which frequently confirms dysplasia but which rarely reveals malignancy. In this article, we describe clinical outcomes, and explore approaches to clinical counselling, risk management and joint decision‐making.